Der Markt fur̈ Fleisch und Fleischprodukte 2022/2023 - Josef Efken; Jakob Meemken; Rebecca Derstappen; Annika Thies (German Journal of Agricultural Economics (GJAE), 2023)
– As in the general public discourse, the development of the various global meat markets in 2022 was dominated by the energy crisis and the resulting cost increases. In addition, epidemics such as African swine fever (ASF) and avian influenza continued to influence market developments. Global beef as well as poultry meat production grew only marginally in 2022. This was offset by strong demand, so 2022 was also characterized by high international price levels overall. Despite weakening international demand for pork - particularly from Chinese importers - pork also became more expensive due to increased production costs. In the EU, pork production fell sharply by 5 % in 2022 compared with 2021. Beef and poultry meat production also fell slightly, while meat imports increased by a quarter. Overall, meat consumption in the EU stagnated. In 2022, the German market was characterized by sharp declines in beef and pork production, which were accompanied by equally sharp declines in demand. Poultry meat production and demand were rather constant.
Keywords: 330